(untitled) (Ágora Journal, 2022)
In the sequence of the advances made after 1985, the rise of bolsonarism marks another moment of reflux of Human Rights (HHRR). So, this article advances on a specific field: the incidence of bolsonarism in higher education, seen as an expression of second-generation HHRR. Based on a qualitative methodology, it hypothetically establishes that, if bolsonarism corresponds to a neoconservative, often fascist worldview, then the policies of the Jair Bolsonaro government for Higher Education will necessarily be restrictive, attacking historical achievements, disarticulating legal-institutional bases and seeking to change the modus operandi of this educational segment. With regard to its results, it is demonstrated that bolsonarism has attacked the right to access to Higher Education both in its principle and in its effectiveness.